The Role of Concussion History and Biological Sex on Pupillary Light Reflex Metrics in Adolescent Rugby Players: A Cross-Sectional Study - Connor McKee; Mark Matthews; Alan Rankin; Chris Bleakley (MDPI AG, 2024)
Background: Concussion examination is based primarily on clinical evaluation and symptomatic reporting. Pupillary light reflex (PLR) metrics may provide an objective physiological marker to inform concussion diagnosis and recovery, but few studies have assessed PLR, and normative data are lacking, particularly for adolescents. Aim: To capture PLR data in adolescent rugby players and examine the effects of concussion history and biological sex. Design: Cross-sectional. Methods: Male and female adolescent rugby union players aged 16 to 18 years were recruited at the start of the 2022-2023 playing season. PLR was recorded using a handheld pupillometer which provided seven different metrics relating to pupil diameter, constriction/dilation latency, and velocity. Data were analysed using a series of 2 × 2 ANOVAs to examine the main effects of independent variables: biological sex, concussion history, and their interactions, using adjusted p-values (p < 0.05). Results: 149 participants (75% male) were included. A total of 42% reported at least one previous concussion. Most metrics were unaffected by the independent variables. There were however significant main effects for concussion history (F = 4.11 (1); p = 0.05) and sex (F = 5.42 (1); p = 0.02) in end pupil diameters, and a main effect for sex in initial pupil diameters (F = 4.45 (1); p = 0.04). Although no significant interaction effects were found, on average, females with a concussion history presented with greater pupillary diameters and velocity metrics, with many pairwise comparisons showing large effects (SMD > 0.8). Conclusions: Pupillary diameters in adolescent athletes were significantly affected by concussion history and sex. The most extreme PLR metrics were recorded in females with a history of concussion (higher pupillary diameters and velocities). This highlights the importance of establishing baseline PLR metrics prior to interpretation of the PLR post-concussion. Long-standing PLR abnormalities post-concussion may reflect ongoing autonomic nervous system dysfunction. This warrants further investigation in longitudinal studies.